Analisis Korelasi Pengetahuan Ibu dengan Perilaku Pencegahan ISPA pada Balita di Puskesmas - Liliek Fauziah; Sari Sarce Andriana; Yosi Andriana Solehah (Jurnal Kesehatan, 2025)
Acute Respiratory Infection (ARI) remains one of the most common diseases affecting toddlers and is a leading cause of morbidity as well as mortality among children in Indonesia. Data from the Bandung District Health Office in 2023 recorded a total of 24,196 ARI cases. One of the factors influencing the prevention of this disease is maternal knowledge. This study aims to determine the relationship between mothers’ levels of knowledge and preventive behaviors against ARI in toddlers at the Cikaro Health Center in Bandung District. This research employed a quantitative, cross-sectional design. The sample consisted of 92 mothers with toddlers diagnosed with ARI, selected using purposive sampling from a population of 120 mothers. The instrument used was a questionnaire. Univariate analysis showed that the majority of respondents had good knowledge (48 respondents, 52.2%) and good preventive behavior (59 respondents, 64.1%). The Chi-square test results indicated a significant relationship between maternal knowledge and preventive behaviors against ARI in toddlers (p = 0.002). With the existence of this relationship, health workers are expected to provide regular education to mothers of toddlers in order to maintain and improve preventive behaviors against ARI, as well as to develop more intensive health promotion programs to reduce the incidence of ARI in toddlers.